A Mixed Methods Design to Detect Adolescent and Young Adults' Impulsiveness on Decision-Making and Motor Performance - Prat, Queralt; Andueza, Juan; Echávarri, Berta; Camerino, Oleguer; Fernandes, Tiago; Castañer, Marta (Frontiers in Psychology, 2019)
Impulsiveness in adolescents and young adults is an important aspect of psychological research. However, there still is lack of research that relates impulsiveness and motor performance in those. Thus, we aim to detect the levels of impulsiveness related to motor skills, motor laterality, spatial orientation and individual interaction on the decision-making of adolescents and young adults across three staggered workouts. The study had 71 participants, (53 males and 18 females) ranging in age from 17 to 24 years old (Mage = 18,5 years; SD = 1,72) and classified as non-impulsiveness (n=47), impulsiveness (n=17) and attention deficit hyperactivity disorder (ADHD) (n=7). A Mixed Methods research was conducted throughout four research tools (a) The Observational System of Motor Skills (OSMOS) was used to observe and detect the movement sequences patterns; (b) The Spanish version of Impulsive Behavior Scale (UPPS-P) was administered to obtain the impulsiveness profiles; (c) The Precision and Agility Tapping over Hoops (PATHoops) was carried out to observe the decision-making and temporal-spatial over movement effectiveness (d) Motor Laterality Inventory (MOTORLAT) was applied to obtain the laterality profiles related to motor skills performance. This Mixed Methods approach has obtained useful results for impulsiveness in motor situations as the results from the different tools converge to established three clear profiles of impulsiveness. Participants with ADHD showed lack of interpersonal interaction, non-resolute decision-making, and lesser richness of motor skills patterns than non-impulsiveness and impulsiveness subjects. Additionally, impulsiveness participants also showed rich motor patterns, dyadic interactions, good decision making in spatial orientation tasks and more versatile laterality in the lower limbs.